Aboriginal Rules: The Black History of Australian Football - Gorman, Sean; Judd, B.; Reeves, K.; Osmond, G.; Klugman, M.; McCarthy, G. (2015)
This paper is interested in the significance of Australian football to the Aboriginal and Torres Strait Islander people of Australia. In particular, this paper is interested in the cultural power of football and how it has foregrounded the struggle and highlighted the contribution that Indigenous people have made to the national football code of Australia. This paper also discusses key moments in Indigenous football history in Australia. It questions further that a greater understanding of this contribution needs to be more fully explored from a national perspective in order to appreciate Indigenous peoples' contribution to the sport not just in elite competitions but also at a community and grass roots level.